Inter-individual Variability in Response to Plant Sterol and Stanol Consumption. (27th November 2019) - Jones, Peter J H
Abstract: Despite the abundance of clinical trial data demonstrating the cholesterol-lowering action of plant sterol supplementation, substantial variability in efficacy exists in responsiveness across individuals. The goal of this review is to examine factors responsible for this heterogeneity in responsiveness of blood cholesterol levels to dietary plant sterols. Although initially thought to be due to random noise in the data, demonstrated consistency in degree of responsiveness in the context of controlled feeding designs from person to person suggests that other systematic drivers are responsible. Genetic explanations explaining this phenomenon appear to be gaining momentum. Particularly, single nucleotide polymorphisms within the genes coding for CYP7A1 and ApoE, as well as possibly other genes including ABCG5 and ABCG8, exist as predictors of whether LDL-C levels will decrease or even increase subsequent to plant sterol administration. In summary, nutrigenetic differences across genes associated with cholesterol trafficking pathways may be important in predicting how well any given individual will respond to dietary interventions. It is anticipated that eventually genetic tests will be developed that can guide health care professionals to optimize dietary strategies for health optimization.